A Development of Nucleic Chromatin Measurements as a New Prognostic Marker for Severe Chronic Heart Failure - Kanzaki, Machiko (PLoS One, 2016)
BACKGROUND: Accurate prediction of both mortality and morbidity is of significant importance, but it is challenging in patients with severe heart failure. It is especially difficult to detect the optimal time for implanting mechanical circulatory support devices in such patients. We aimed to analyze the morphometric ultrastructure of nuclear chromatin in cardiomyocytes by developing an original clinical histopathological method. Using this method, we developed a biomarker to predict poor outcome in patients with dilated cardiomyopathy (DCM). METHODS AND RESULTS: As a part of their diagnostic evaluation, 171 patients underwent endomyocardial biopsy (EMB). Of these, 63 patients diagnosed with DCM were included in this study. We used electron microscopic imaging of cardiomyocyte nuclei and an automated image analysis software program to assess whether it was possible to detect discontinuity of the nuclear periphery. Twelve months after EMB, all patients with a discontinuous nuclear periphery (Group A, n = 11) died from heart failure or underwent left ventricular assist device (VAD) implantation. In contrast, in patients with a continuous nuclear periphery (Group N, n = 52) only 7 patients (13%) underwent VAD implantation and there were no deaths (p<0.01). We then evaluated chromatin particle density (Nuc-CS) and chromatin thickness in the nuclear periphery (Per-CS) in Group N patients; these new parameters were able to identify patients with poor prognosis. CONCLUSIONS: We developed novel morphometric methods based on cardiomyocyte nuclear chromatin that may provide pivotal information for early prediction of poor prognosis in patients with DCM.